"A tool doesn't add anything". The importance of added value: Use of observational pain tools with patients with advanced dementia approaching the end of life—a qualitative study of physician and nurse experiences and perspectives. (1st July 2018) - De Witt Jansen, Bannin; Brazil, Kevin; Passmore, Peter; Buchanan, Hilary; Maxwell, Doreen; McIlfatrick, Sonja; Morgan, Sharon M.; Watson, Max; Parsons, Carole
Abstract : Background: Observational pain tools (OPTs) are widely recommended in health care policies, clinical guidelines, and recommendations for pain assessment and management. However, it is unclear whether and how these tools are used for patients with advanced dementia approaching the end of life. Aim: To explore hospice, secondary, and primary care physicians' and nurses' use of OPTs with patients dying with advanced dementia and their perspectives on practice development and training needs. Methods: Twenty‐three physicians and 24 nurses with experience of caring for people dying with advanced dementia were recruited from primary care surgeries (n = 5), hospitals (n = 6), hospices (n = 4), and nursing homes (n = 10). Semistructured, face‐to‐face interviews were conducted. Interviews were digitally recorded, transcribed verbatim, and thematic analysis applied to identify core themes. Results: Three key themes emerged: (1) use of OPTs in this vulnerable patient population, (2) barriers to the use of OPTs and lack of perceived "added value", and (3) perspectives on practice development and training in pain assessment in advanced dementia at end of life. Just over one‐quarter of participants (n = 13) routinely used OPTs. Reasons for nonuse included perceived limitations of such tools, difficulties with their use and integration with existing practice, and lack of perceived added value. Most participants strongly emphasised a need for ongoing training and development which facilitated transfer of knowledge and multidisciplinary skills across professions and specialties. Conclusions: Health professionals require ongoing support in developing and integrating change to existing pain assessment protocols and approaches. These findings have important implications for health education, practice, and policy.